Talent attraction and retention in the restaurant sector: an overview - Maia , Beatriz; Melo , António; Silva, Susana (Conferência - Investigação e Intervenção em Recursos Humanos, 2023)
In the current life of organizations providing food services, a new logic is perceptible: instability, volatility, and disconcerting any observer in search of regularities and trends. The market is increasingly competitive, and customers are increasingly demanding, so organizations in this sector have had to adapt to this new reality and differentiate themselves through greater efficiency and effectiveness in the management of their resources. The focus of this study is to address the challenges of Human Resource Management (HRM) in the restaurant sector. This research aims to characterize the previous studies about the attraction and retention process in the restaurant sector. The importance of this study is justified by the high turnover of employees, long working hours, physical and emotional wear, low salaries, some informality in the work, and tear is one of the greatest difficulties faced by the sector, directly affecting the quality of service, company profits, and employee satisfaction. This study is carried out in a post-pandemic scenario, caused by COVID-19, where the need to adapt strategic HRM is imperative. This study is expected to provide valuable insight into the challenges facing the catering industry in attracting and retaining employees, helping companies take steps to improve employee satisfaction and increase talent retention. In addition, it is expected that this study can contribute to the general understanding of the dynamics of the labor market in the field of catering.